Modal Spiritual Islam Pada Pengelola Pondok Pesantren Darul Hikmah Burneh Bangkalan - Dharodjah, Ulya (Jurnal Ilmiah Ekonomi Islam, 2024)
The purpose of this research is to find out the Islamic spiritual capital that exists in the manager of Darul Hikmah Burneh Bangkalan Islamic Boarding School. The method in this study uses Islamic phenomenology qualitative research method through field observations and interviews with informants to see how the implementation of Islamic Spiritual Capital in the manager of Darul Hikmah Burneh Bangkalan Islamic Boarding School. The results of this study indicate that the Islamic spiritual capital that exists in the management of the Darul Hikmah Burneh Islamic Boarding School includes sincerity, discipline (istiqomah), ukhuwah Islamiyah, Islamic governance and leadership, which can educate and mould students into individuals who behave ihsan, and under the auspices of the pillars of Faith and the pillars of Islam as a foundation.